Possibilities in Artistic Practices: Human Rights and Training for a Culture of Citizenship (Global Journal of Human-Social Science, 2021)
This text reflects on the practice in art education to develop curiosity interest and critical thinking on issues concerning freedom of creative expression and the creation of significant artistic manifestations that communicate with the other The learning processes based on dialogue and relational collaboration between students and teachers result in artistic objects produce from reflection around issues of human rights and formation for citizenship The study was developed in the Artistic Production Course of the Specialization in Ceramics at Ant nio Arroio Art School in Lisbon Portugal with students from a 12th-grade class An action-research methodology was used with data collected through the observation of the developed activities and interviews intended to understand and identify connections arising from these reflective thoughts and their impact on artistic practices Within the scope of the results obtained we found that promoting activities with experimentation and exploration of ideas sharing different perspectives and decision-making contributes to the social and cultural individuals identity construction
Keywords: artistic practices; human rights; social and cultural citizenship; social transformation